Cholera toxin binds to lipid rafts but has a limited specificity for ganglioside GM1 - Blank, Norbert; Schiller, Martin; Krienke, Stefan; Wabnitz, Guido H.; Ho, Anthony Dick; Lorenz, Hanns-Martin (Immunology & cell biology, 2007)
Lipid rafts and the formation of an immunological synapse are crucial for T-cell activation. Binding of cholera toxin B subunit (CTB) to ganglioside GM1 is a marker to identify lipid rafts. Primary human T cells were isolated from healthy donors and were stimulated with superantigen staphylococcus enterotoxin B (SEB) and stained with cholera toxin B-fluorescein isothiocyanate (CTB-FITC). An optimized staining procedure is required to stain lipid rafts exclusively on the cell surface. Unstimulated T cells show a few CTB binding spots on the cell surface. The size and number of CTB-binding lipid rafts are strongly upregulated during T-cell activation in SEB-stimulated CD4+ T cells. However, our data show that the specificity of CTB for GM1 ganglioside is limited, because the binding capacity is partly resistant to inhibition of ganglioside synthesis and sensitive to trypsin digestion. Our results indicate that the binding of FITC-labeled CTB can be divided into at least three different categories: a specific binding of CTB to ganglioside GM1, a nonspecific binding of CTB probably to glycosylated surface proteins and a nonspecific binding of FITC to the cell surface.
Gesehen am 18.10.2021